Small bowel fistula and its impact: incorrect placement of left ventricular assist device cannulas leads to severe intestinal complications. (15th September 2011) - Yilmaz, Kadir; Erpenbeck, Heinrich; Drews, Thorsten; Hetzer, Roland
Abstract : A young man presented with a chronic abdominal dermal irritation 4 years after implantation of a left ventricular assist device (LVAD; Berlin heart excor). The LVAD was needed because of end-stage heart failure following a chronic parvovirus B19 Infection. The implantation of mechanical circulatory support systems (MCS) has nowadays become an accepted treatment modality for patients with end-stage heart failure. Recent literature shows several intestinal complications related to MCS, but no case presents the development of a small bowel fistula to the jejunum, transversal colon and stomach. We present a case of inaccurate placement of Berlin heart excor LVAD cannulas and its impact. This case emphasises the importance of correct placement of VAD cannulas to achieve an optimal long-term result. After surgical treatment the postoperative course was prolonged because of increasing peritonitis probably based on ongoing intraperitoneal chronic contamination with intestinal germs. The patient unfortunately deceased.